PROMOTING TECHNOLOGY-BASED LEARNING IN NIGERIA: ROLE OF THE STAKEHOLDERS - Ademiotan Moriyike Laleye (Paedagogia: Jurnal Pendidikan, 2022)
This study investigated the roles of stakeholders in promoting technology-based learning in Nigeria. The population of the study comprised all senior secondary school III students in public secondary schools, their teachers and parents in Akoko South West, Ondo State. Simple random procedure was used to select ten (10) schools out of seventeen (17) secondary schools in the Local Government. Four hundred (400) samples comprised 300 students, 50 teachers and 50 parents were randomly selected from the population. Self-developed questionnaire served data collection purpose. The validated instrument, has a reliability index of 0.68. Findings from the study revealed that parents are to provide ICT gadgets for their children at home and monitor them so as to guide against abuse of the technology; it was discovered that Government, P.T.A., old students, philanthropists are to build and equip ICT units in schools and to, organize workshops and seminars for teachers on ICT. It was concluded that building and equipping of ICT centers by the government is very germane, PTA old students association and philanthropists. However, teachers are to strategically and technically make use of technology to foster teaching and learning in Nigeria. It was recommended that workshop and seminars are to be organized for personnel in ICT in schools by the Government and teachers are to use new innovative method to blend learning and make the process technology-based.Key words: stakeholders, parents, old students, technology-based, learning.